Graphene quantum dots induced porous orientation of holey graphene nanosheets for improved electrocatalytic activity. (January 2021) - Ali, Mumtaz; Riaz, Rabia; Anjum, Aima Sameen; Sun, Kyung Chul; Li, Hui; Jeong, Sung Hoon; Ko, Min Jae
Abstract: Complex electrolyte diffusion through the stacked graphene nanosheets limits their electrochemical performance. As a potential solution, this study explored the potential of nitrogen-doped graphene quantum dots (NGQDs) to induce 3D porous orientation of holey graphene oxide (hGO) nanosheets. The sizes of NGQDs and antisolvent for phase separation assisted assembly were optimized to achieve a 3D nanoporous network. This nano-network serves as a soft template for the porous orientation of hGO, forming a 3D hierarchically porous carbon architecture. Benefiting from the porosity of the 3D framework, π-π restacking was radically avoided, providing high electrolyte transport rates. In addition, doped nitrogen and J-type aggregation of NGQDs effectively tuned the band structure to realize charge transfer at low overpotential. The enhanced electrocatalytic activity and exceptionally low charge transfer resistance of the composite structure were attributed to the enhanced electrode/electrolyte interface and multidimensional charge & electrolyte transport. Porous composite structure based counter electrode showed 78% enhanced photovoltaic performance (compared to unmodified graphene) in the dye-sensitized solar cell, which is comparable to the performance of Pt electrode. The proposed 3D porous orientation can be utilized in emerging electrocatalytic applications, such as supercapacitors, water splitting, and battery electrodes. Graphical abstract: Figure showing the porous orientation of bigger "holey graphene oxide sheets" by realizing a strong phase separation assembly of smaller "graphene quantum dots". Such an orientation mechanism can be related to ants: as they can lift heavier loads than their weight. Image 1 Highlights: Ultrastrong phase-separated assembly of GQDs was realized by optimizing size and antisolvent. GQDs assembly serves as a soft template for the porous orientation of hGO sheets. NGQDs assisted orientation of hGO shows Pt like electrocatalytic activity.